2015
DOI: 10.1093/hmg/ddv441
|View full text |Cite
|
Sign up to set email alerts
|

Multikinase activity of fibroblast growth factor receptor (FGFR) inhibitors SU5402, PD173074, AZD1480, AZD4547 and BGJ398 compromises the use of small chemicals targeting FGFR catalytic activity for therapy of short-stature syndromes

Abstract: Activating mutations in the fibroblast growth factor receptor 3 (FGFR3) cause the most common genetic form of human dwarfism, achondroplasia (ACH). Small chemical inhibitors of FGFR tyrosine kinase activity are considered to be viable option for treating ACH, but little experimental evidence supports this claim. We evaluated five FGFR tyrosine kinase inhibitors (TKIs) (SU5402, PD173074, AZD1480, AZD4547 and BGJ398) for their activity against FGFR signaling in chondrocytes. All five TKIs strongly inhibited FGFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 52 publications
0
49
0
Order By: Relevance
“…However, these TKIs are not selective for FGFR3 (Mohammadi et al, 1997; Dimitroff et al, 1999). Recently, NVP-BGJ398, a TKI more selective for FGFR3 over others FGFRs (Gudernova et al, 2016) was used in preclinical murine models for treating several FGFR-related cancers such as malignant rhabdoid tumors (Wohrle et al, 2013b), hepatocellular carcinoma (Scheller et al, 2015) and skeletal disorders including FGF23-mediated hypophosphatemic rickets (Wohrle et al, 2013a) and Ach (Komla-Ebri et al, 2016). Importantly, NVP-BGJ398 was shown in vivo to reduce FGFR3(p.Tyr367Cys) activation and improve the skeletal phenotype of Ach-like mice (Komla-Ebri et al, 2016).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…However, these TKIs are not selective for FGFR3 (Mohammadi et al, 1997; Dimitroff et al, 1999). Recently, NVP-BGJ398, a TKI more selective for FGFR3 over others FGFRs (Gudernova et al, 2016) was used in preclinical murine models for treating several FGFR-related cancers such as malignant rhabdoid tumors (Wohrle et al, 2013b), hepatocellular carcinoma (Scheller et al, 2015) and skeletal disorders including FGF23-mediated hypophosphatemic rickets (Wohrle et al, 2013a) and Ach (Komla-Ebri et al, 2016). Importantly, NVP-BGJ398 was shown in vivo to reduce FGFR3(p.Tyr367Cys) activation and improve the skeletal phenotype of Ach-like mice (Komla-Ebri et al, 2016).…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…The alignment of the deduced amino acid sequence of zebrafish Fgfr3 with that of its human homolog (FGFR3) shows a high level of homology between the two proteins (77% overall, and more than 90% when considering the tyrosine kinase domain alone; Figure 1 -supplement 1). In order to investigate Fgfr3's role, we used the tyrosine kinase inhibitor BGJ398 (infigratinib, LC Laboratories) to block the factor's tyrosine kinase activity during cranial vault development (Gudernova et al, 2016;Komla-Ebri et al, 2016). Zebrafish larvae with a standard length (SL) of 7 mm (7SL) and expressing mCherry in osteoblasts (Tg(sp7: mCherry) were injected with BGJ398 every other day for 15 days ( Figure 1A).…”
Section: Inhibition Of Fgfr3's Tyrosine Kinase Activity Affects Cranimentioning
confidence: 99%
“…A recent study showed that the efficacy of five small molecule FGFR inhibitors, while effective in chondrocytes in vitro , did not improve skeletal growth in mice. Troublingly, they had no selectivity for FGFR3, but had significant off-target activity for IGFR1 [43]. These data show that new innovative approaches to treat achondrodysplasia are still required.…”
Section: Fibroblast Growth Factor (Fgf) Signalingmentioning
confidence: 99%